Activity-based cost (ABC), for the accommodation activity (Costos y Gestión, 2021)
The research work presented focuses on the proposal for calculating Activity-Based Cost at the El Yunque deBaracoa Base Business Unit located in the municipality of Baracoa, belonging to the Camping Company PopularGuantánamo, with the aim of proposing a procedure to calculate the Activity Based Cost , based on thestudy of the processes in the accommodation area of the UEB in question. The proposed procedure will facilitatethe decision-making of UEB managers, since the current cost system lacks information to efficiently man-age the accommodation activity that the client demands. A wide search was made of criteria from differentauthors, on the evolution of Management Accounting, analyzing its main contributions and demonstratingthe advantages of ABC over traditional costs. As a result of the research, it will improve the way of managingthe resources and activities that are consumed and executed, allowing the company management to guidethe implementation of this procedure to the rest of the UEB.
Keywords: activity based cost; decision making